Use of renewable energy for desalination in urban agriculture in the GCC countries: Possibilities and challenges - Salem Al-Jabri; Mushtaque Ahmed (Journal of Agricultural and Marine Sciences, 2018)
The current dependence of the GCC countries on fossil oil and gas is unwise in terms of economic and environmental sustainability. GCC countries must consider the use of renewable energy to cope with price fluctuations of oil and gas in the global market and to lower the emission of green house gases. The demand for food and water in the GCC countriesis increasing due to high growth rate of population. Given the weather conditions and available amounts of natural water resources, the demand on food and water cannot be met unless alternative sources of water are considered. Several studies pointed out that the desalination technology is probably the only option for producing ample amounts of water for food production in arid environments. This work explores the potential of use of desalination technology for producing irrigation water in GCC countries, with special emphasis on experience of the Sultanate of Oman compared with that of Spain. Desalination can always provide a tailored-quality irrigation water at any climatic conditions. The main challenge for considering desalination for agriculture is purely economic; where GCC countries could consider it only if intensive horticulture of high-value cash crops, such as vegetables and flowers in controlled environments, is considered. Disposal of brine water is also a challenge and must be done at an additional cost. Depending on the quality of desalinated water, several studies showed that solar-operated desalination technologies are in a mature stage and economically viable. Therefore, solar energy can make the desalination technology an attractive option to sustain agriculture and food supply in GCC countries.